2016
DOI: 10.1007/s00401-016-1554-0
|View full text |Cite
|
Sign up to set email alerts
|

ECEL1 mutation implicates impaired axonal arborization of motor nerves in the pathogenesis of distal arthrogryposis

Abstract: The membrane-bound metalloprotease endothelin-converting enzyme-like 1 (ECEL1) has been newly identified as a causal gene of a specific type of distal arthrogryposis (DA). In contrast to most causal genes of DA, ECEL1 is predominantly expressed in neuronal cells, suggesting a unique neurogenic pathogenesis in a subset of DA patients with ECEL1 mutation. The present study analyzed developmental motor innervation and neuromuscular junction formation in limbs of the rodent homologue damage-induced neuronal endope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Furthermore, in three patients (A1, A2 and B2), we noted the presence of fibres positive for nCAM suggesting a possible problem with innervation of some fibres ( Fig.4c and 4f). This finding supports the hypothesis, gathered from the Ecel1 mouse model, that the lack of peripheral motor axon arborisation contributes to the pathogenesis of DAD5 [19]. Analysis of muscle biopsies of further patients with ECEL1 gene mutations might help to clarify this point and to characterize further the histopathological spectrum of this condition, assessing if the condition is neurological rather than muscular in origin.…”
Section: Accepted Manuscriptsupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, in three patients (A1, A2 and B2), we noted the presence of fibres positive for nCAM suggesting a possible problem with innervation of some fibres ( Fig.4c and 4f). This finding supports the hypothesis, gathered from the Ecel1 mouse model, that the lack of peripheral motor axon arborisation contributes to the pathogenesis of DAD5 [19]. Analysis of muscle biopsies of further patients with ECEL1 gene mutations might help to clarify this point and to characterize further the histopathological spectrum of this condition, assessing if the condition is neurological rather than muscular in origin.…”
Section: Accepted Manuscriptsupporting
confidence: 85%
“…The jitter measurement was normal in three patients of our series examined by this means, effectively ruling out a neuromuscular junction defect. This is relevant in view of the suggestion, from the Ecel1 mouse model, of a contribution of the neuromuscular junction in the disease pathogenesis [19]. From a clinical diagnostic point of view, in view of the major clinical and pathological overlap with similar myopathic contractural syndromes, we strongly suggest adding ECEL1 gene into panel of genes responsible for congenital myopathies and / or distal arthrogryposis.…”
Section: Accepted Manuscriptmentioning
confidence: 88%
See 1 more Smart Citation
“…22, 23 Subsequently, we have found that aberrant arborization of motor axons and failure of neuromuscular formation can be a primary cause of DA with the ECEL1 mutation. 24 In line with this, it is likely that DINE has an important role as a protease in the neurons where its expression is abundant.…”
mentioning
confidence: 90%
“…13,14 Ecel1 knock-in mice with a pathogenic mutation causing type 5 DA have defects in the axonal arborization of the motor nerves in the limbs, suggesting that failure of the neuromuscular junctions could be the primary cause of DA in patients with Ecel1 mutation. 15 Ecel1 gene expression is synergistically regulated by axonal regeneration-associated transcriptional factors, such as ATF3, c-Jun, and STAT3, through the activation of Sp1. 16 This suggests that Ecel1 is associated with axonal regeneration.…”
mentioning
confidence: 99%